2010
DOI: 10.1002/yea.1769
|View full text |Cite
|
Sign up to set email alerts
|

The quorum‐sensing molecule E,E‐farnesol—its variable secretion and its impact on the growth and metabolism of Candida species

Abstract: Diseases caused by Candida species are an increasing problem. Candida species are associated with high overall mortality, due to a variety of virulence factors such as the yeast-to-hyphal switch and proteolytic enzymes. The phenomenon of microbial communication known as quorum sensing also seems to play an important role. The main characteristics of the quorum-sensing molecule E ,E -farnesol are well known for C. albicans. The present study focused on two questions. One of them concerned the secretion of E ,E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 43 publications
7
49
0
Order By: Relevance
“…In an experimental protocol that induce hyphae formation through the presence of BSA in the culture medium, we showed that farnesol reduced, up to 10-fold, the Candida transition from yeast to hyphal forms. These data are in accordance with previously reported studies [36] showing that farnesol (which acts in an autocrine manner on Candida ) blocks the morphological shift of Candida from yeast to hyphae at high cell densities [37, 38]. This was confirmed by in vitro studies showing that exogenously-added farnesol inhibited germ tube formation [39-41] normally triggered by serum [32], proline and N -acetylglucosamine [24].…”
Section: Discussionsupporting
confidence: 92%
“…In an experimental protocol that induce hyphae formation through the presence of BSA in the culture medium, we showed that farnesol reduced, up to 10-fold, the Candida transition from yeast to hyphal forms. These data are in accordance with previously reported studies [36] showing that farnesol (which acts in an autocrine manner on Candida ) blocks the morphological shift of Candida from yeast to hyphae at high cell densities [37, 38]. This was confirmed by in vitro studies showing that exogenously-added farnesol inhibited germ tube formation [39-41] normally triggered by serum [32], proline and N -acetylglucosamine [24].…”
Section: Discussionsupporting
confidence: 92%
“…1). The C. albicans cell can reduce its metabolic activity as a protective mechanism under adverse conditions [22], [23]. Therefore, we studied the effects of S-8 on morphology and viability of the biofilm cells.…”
Section: Resultsmentioning
confidence: 99%
“…Within the Candida clade, C. albicans produces the highest amounts of farnesol, with levels reaching up to 55 mM in dense C. albicans cultures (Weber, Schulz, & Ruhnke, 2010;Weber, Sohr, Schulz, Fleischhacker, & Ruhnke, 2008). Farnesol has several effects on C. albicans.…”
Section: The Quorum Sensing Molecule Farnesol and Cellular Signalingmentioning
confidence: 99%